WATERFALL MODEL IMPLEMENTATION IN INFORMATION SYSTEMS WEB BASED GOODS DELIVERY SERVICE - Reni Haerani; Penny Hendriyati; Praditya Adi Nugroho; Muhammad Lukman (STMIK Royal, 2023)
Abstract: This study discusses the delivery information system for the minimarket 212 Mart. Minimarket 212 Mart is a modern retail business. The purpose of this research is to simplify and shorten the process of computerized goods distribution services to prevent data input errors, reduce disappointment due to customer service errors, expedite, and simplify service procedures between operational goods owners, and make it easier for the owner to receive a summary of shipping information. The research method used is the waterfall model. The problem with ordering goods is that customers are still using Whatsapp and those who order are still in the local area, not far from the mini market, thereby reducing sales. In addition, standard writing instruments are still used to record the delivery and receipt of goods. When delivering goods, customers buy directly from the convenience store, and it is difficult for customers to track the location of the goods ordered. Therefore, it must be built and designed with a software system that facilitates transportation registration, the processing of sales invoices, and the preparation of reports. Program design modeling applies to data flow diagrams and entity relationship diagrams. The software used is the PHP programming language and the MySQL database. The research artificial achieved are a web-based goods delivery service system that must overcome the problems that exist in goods delivery services at 212 Mart Serang-Banten Minimarket.Keywords: Information System, Delivery Service, Waterfall, Web Abstrak: Penelitian ini membahas sistem informasi pengiriman barang minimarket 212 Mart. Minimarket 212 Mart merupakan salah satu usaha ritel modern. Maksud dari riset ini adalah untuk mempermudah dan mempersingkat proses pelayanan pendistribusian barang secara terkomputerisasi untuk mencegah terjadinya kesalahan input data, mengurangi kekecewaan akibat kekeliruan pelayanan atas pelanggan dan melancarkan serta mempermudah prosedur servis antar operasional pemilik barang serta memudahkan owner menerima ringkasan informasi pengiriman. Metode riset yang dipakai adalah model waterfall. Kendala pemesanan barang masih menggunakan Whatsapp, pelanggan yang memesan masih berada di area lokal yang tidak jauh dari mini market, sehingga mengurangi penjualan. Selain itu, alat tulis standar masih digunakan untuk mencatat pengiriman dan penerimaan barang. Saat mengirimkan barang, pelanggan membeli langsung dari minimarket, dan sulit bagi pelanggan untuk melacak lokasi barang yang dipesan. Oleh sebab itu, harus dibangun dan merancang sistem perangkat lunak yang memudahkan pendaftaran pengangkutan, pengerjaan faktur penjualan, dan penyusunan laporan. Pemodelan desain program menerapkan Data Flow Diagram dan Entity Relationship Diagram. Perangkat lunak yang dipergunakan adalah bahasa pemrograman PHP dan database MySQL. Artifisial penelitian yang dicapai merupakan sistem layanan pengiriman barang berbasis web yang harus melampaui permasalahan yang ada pada layanan pengiriman barang di minimarket 212 Mart Serang-Banten.Kata kunci: Sistem Informasi, Delivery Service, Waterfall, Web